Association between expectation of self-efficacy and adherence to antiretroviral treatment in adults with HIV (Research, Society and Development, 2021)
Objective: To evaluate the association between the expectation of self-efficacy and adherence to antiretroviral treatment in adults with HIV. Method: Cross-sectional study developed in a specialized service in southern Brazil with 156 participants. The Self-Efficacy Expectation Scale for Following Antiretroviral Prescription and the Assessment of Adherence to Antiretroviral Therapy Questionnaire (CEAT-VIH) were applied. Spearman correlation analysis. Results: The experiences of annoyance, discrimination, rejection, insecurity due to the reaction of other people (in close contact) due to the diagnosis. Additionally, nervousness, irritation, ingestion of large amounts of pills and other adverse effects caused by the medication were found to be significantly correlated with overall adherence. Conclusion: Negative experiences with the use of medications and those experienced in social relationships had lower means for self-efficacy and greater correlation between self-efficacy and adherence, indicating the need to deconstruct the stigma.